اجتہاد کا تاریخی پس منظراور معاصر ممکنہ صورتیں؛ ایک تجزیاتی مطالعہ: Historical background of ijtihad and its Possibilities in modern era; An analytical study - Rabbani, Muhammad Aslam (Al-Amīr Research Journal for Islamic Studies, 2023)
Ijtihad is an important term in Islamic Shari'ah which refers to the human being's ability to derive Islamic rulings from their specific sources and benefits. The Messenger of Allah ﷺalso engaged in ijtihad on some occasions during his time, after which the companions of the Prophet ﷺ also continued to do ijtihad in their respective periods. His method was that first of all he would look at the Qur'an and then look for the same problems from the Hadith. In the said article, while clarifying the background of Ijtihad, its importance, procedure and possible cases will be discussed in the present era. At the same time, it will be highlighted that what is the scope of ijtihad and what issues need ijtihad in the present era. Key Words: Ijtihad, Qur’an, Sunnah, Companion, Jurists, Authenticity, Contemporary Forms.